Compilation of Commit Changes Within Java Source Code Repositories - Schott, Stefan; Fischer, Wolfram; Ponta, Serena Elisa; Klauke, Jonas; Bodden, Eric (2024 IEEE International Conference on Software Maintenance and Evolution (ICSME))

Quality Key Figures for Developing Future Scenarios - Gräßler, Iris; Özcan, Deniz (AHFE International)

Zwischen Ästhetik und Funktion. Begriffstheoretische Perspektiven auf digitale Mode - Brachtendorf, Charlotte (Annali. Sezione germanica)

Policy advice and best practices on bias and fairness in AI - Alvarez, Jose M.; Colmenarejo, Alejandra Bringas; Elobaid, Alaa; Fabbrizzi, Simone; Fahimi, Miriam; Ferrara, Antonio; Ghodsi, Siamak; Mougan, Carlos; Papageorgiou, Ioanna; Reyero, Paula; Russo, Mayra; Scott, Kristen M.; et al. (Ethics and Information Technology)
Abstract The literature addressing bias and fairness in AI models ( fair-AI ) is growing at a fast pace, making it difficult for novel researchers and practitioners to have a bird’s-eye view picture of the field. In particular, many policy initiatives, standards, and best practices in fair-AI have been proposed for setting principles, procedures, and knowledge bases to guide and operationalize the management of bias and fairness. The first objective of this paper is to concisely survey the state-of-the-art of fair-AI methods and resources, and the main policies on bias in AI, with the aim of providing such a bird’s-eye guidance for both researchers and practitioners. The second objective of the paper is to contribute to the policy advice and best practices state-of-the-art by leveraging from the results of the NoBIAS research project. We present and discuss a few relevant topics organized around the NoBIAS architecture, which is made up of a Legal Layer, focusing on the European Union context, and a Bias Management Layer, focusing on understanding, mitigating, and accounting for bias.

Articulation Work and Tinkering for Fairness in Machine Learning - Fahimi, Miriam; Russo, Mayra; Scott, Kristen M.; Vidal, Maria-Esther; Berendt, Bettina; Kinder-Kurlanda, Katharina (Proceedings of the ACM on Human-Computer Interaction)
The field of fair AI aims to counter biased algorithms through computational modelling. However, it faces increasing criticism for perpetuating the use of overly technical and reductionist methods. As a result, novel approaches appear in the field to address more socially-oriented and interdisciplinary (SOI) perspectives on fair AI. In this paper, we take this dynamic as the starting point to study the tension between computer science (CS) and SOI research. By drawing on STS and CSCW theory, we position fair AI research as a matter of 'organizational alignment': what makes research 'doable' is the successful alignment of three levels of work organization (the social world, the laboratory, and the experiment). Based on qualitative interviews with CS researchers, we analyze the tasks, resources, and actors required for doable research in the case of fair AI. We find that CS researchers engage with SOI research to some extent, but organizational conditions, articulation work, and ambiguities of the social world constrain the doability of SOI research for them. Based on our findings, we identify and discuss problems for aligning CS and SOI as fair AI continues to evolve.

In/visibilities in Data Studies: Methods, Tools, and Interventions - Fahimi, Miriam; Falk, Petter; Gray, Jonathan W. Y.; Jarke, Juliane; Kinder-Kurlanda, Katharina; Light, Evan; McGeachey, Ellouise; Perea, Itzelle Medina; Poechhacker, Nikolaus; Poirier, Lindsay; Röhle, Theo; Sharon, Tamar; et al. (Dialogues in Data Power)
This chapter highlights the intricate nature of data and their profound social implications. It examines the acts of rendering data visible and the inherent power dynamics and imbalances that accompany such processes. Our dialogue unfolds in three interconnected parts, each focusing on the intersection of in/visibility and power. Part 1 attends to the challenges of producing knowledge about and with data, emphasizing the relativity, fluidity, and instability inherent in data. It explores frameworks that uncover the often invisible infrastructures of algorithms, rendering visible the actors, technologies, and divergent values involved in data manipulation. Part 2 presents empirical case studies that analyse the consequences of data visibility while contemplating the methodological opportunities and challenges of foregrounding the embedded values and norms within data. Part 3 discusses tool-based interventions aimed at bringing alternative data framings and narratives to the fore. It examines the complexities of tracing data across various contexts and the value, utility, and obstacles associated with creating visual representations of data and their flows. By critically engaging with the complexities of data in/visibility, this chapter challenges existing gatekeepers and fosters a deeper understanding of the multifaceted nature of data and its socio-political ramifications.

Making Algorithms Fair: Ethnographic Insights from Machine Learning Interventions - Kinder-Kurlanda, Katharina; Fahimi, Miriam (Algorithmic Regimes. Methods, Interactions, and Politics.)
Algorithms have risen to become one, if not the central technology for producing, circulating, and evaluating knowledge in multiple societal arenas. In this book, scholars from the social sciences, humanities, and computer science argue that this shift has, and will continue to have, profound implications for how knowledge is produced and what and whose knowledge is valued and deemed valid. To attend to this fundamental change, the authors propose the concept of algorithmic regimes and demonstrate how they transform the epistemological, methodological, and political foundations of knowledge production, sensemaking, and decision-making in contemporary societies. Across sixteen chapters, the volume offers a diverse collection of contributions along three perspectives on algorithmic regimes: the methods necessary to research and design algorithmic regimes, the ways in which algorithmic regimes reconfigure sociotechnical interactions, and the politics engrained in algorithmic regimes.

Corrosion fatigue behavior of nanoparticle modified iron processed by electron powder bed fusion - Wackenrohr, Steffen; Torrent, Christof Johannes Jaime; Herbst, Sebastian; Nürnberger, Florian; Krooss, Philipp; Frenck, Johanna-Maria; Ebbert, Christoph; Voigt, Markus; Grundmeier, Guido; Niendorf, Thomas; Maier, Hans Jürgen (npj Materials Degradation)
Abstract Due to its excellent biocompatibility, pure iron is a very promising implant material, but often features corrosion rates that are too low. Using additive manufacturing and modified powders the microstructure and, thus, the material properties, e.g., the corrosion properties, can be tailored for specific applications. Within the scope of this study, pure iron powder was modified with different amounts of CeO 2 or Fe 2 O 3 nanoparticles and subsequently processed by Electron Beam Powder Bed Fusion (PBF-EB/M). The corrosion-fatigue behavior of CeO 2 and Fe 2 O 3 modified iron was investigated using rotation bending tests under the influence of simulated body fluid (m-SBF). While the modification using Fe 2 O 3 showed reduced fatigue and corrosion-fatigue strengths, it could be demonstrated that the modification with CeO 2 is characterized by improved fatigue properties. The superior fatigue properties in air are attributed to the positive impact of dispersion strengthening. Additionally, an increased degradation rate compared to pure iron could be observed, eventually promoting an earlier failure of the specimens in the corrosion fatigue tests.

Cell stress and phase separation stabilize the monomeric state of pseudoisocyanine chloride employed as a self-assembly crowding sensor - Pollak, Roland; Koch, Leon; König, Benedikt; Ribeiro, Sara S.; Samanta, Nirnay; Huber, Klaus; Ebbinghaus, Simon (Communications Chemistry)
Abstract Cellular stress and ageing involve an increase in crowding and aggregation of amylogenic proteins. We here investigate if crowding is the intrinsic cause of aggregation and utilise a previously established non-protein aggregation sensor, namely pseudoisocyanine chloride (PIC). PIC shows fibrillization in cells into a highly fluorescent J-aggregated state and is sensitive to crowding. Surprisingly, cell stress conditions stabilise the monomeric rather than the aggregated state of PIC both in the cytoplasm and in stress granules. Regarding the different physiochemical changes of the cytoplasm occurring upon cell stress, involving volume reduction, phase separation and solidification, the intrinsic crowding effect is not the key factor to drive associated self-assembly processes.

Molecular Crowding: The History and Development of a Scientific Paradigm - Alfano, Caterina; Fichou, Yann; Huber, Klaus; Weiss, Matthias; Spruijt, Evan; Ebbinghaus, Simon; De Luca, Giuseppe; Morando, Maria Agnese; Vetri, Valeria; Temussi, Piero Andrea; Pastore, Annalisa (Chemical Reviews)

Impact of Additive Hydrophilicity on Mixed Dye-Nonionic Surfactant Micelles: Micelle Morphology and Dye Localization - Müller, Wenke; Sroka, Weronika; Schweins, Ralf; Nöcker, Bernd; Poon, Jia-Fei; Huber, Klaus (Langmuir)

On the Mechanism of Self-Assembly of Fibrinogen in Thrombin-free Aqueous Solution - Saha, Sanjib; Büngeler, Anne; Hense, Dominik; Strube, Oliver I.; Huber, Klaus (Langmuir)

Impact of Temperature on the Self-Assembly of Fibrinogen in Thrombin-Free Solutions - Koch, Leon; Saha, Sanjib; Huber, Klaus (The Journal of Physical Chemistry Letters)

Early Stages of FUS Droplet Formation via Liquid–Liquid Phase Separation - Koch, Leon; Pollak, Roland; Ebbinghaus, Simon; Huber, Klaus (Langmuir)

Rezension zu: „Manuscripts and Performances in Religions, Arts, and Sciences” - Bergmann, Claudia Dorit (tà katoptrizómena – Magazin für Kunst | Kultur | Theologie | Ästhetik 151)

Rezension zu: „The Song of Songs through the Ages. Essays on the Song’s Reception History in Different Times, Contexts, and Genres” - Bergmann, Claudia Dorit (tà katoptrizómena – Magazin für Kunst | Kultur | Theologie | Ästhetik 151)

Rezension zu: „Manuscripts and Performances in Religions, Arts, and Sciences” - Bergmann, Claudia Dorit (tà katoptrizómena – Magazin für Kunst | Kultur | Theologie | Ästhetik 151)

Rezension zu: „Manuscripts and Performances in Religions, Arts, and Sciences.” - Bergmann, Claudia Dorit (, tà katopt- rizómena – Magazin für Kunst | Kultur | Theologie | Ästhetik 151)

Christian Marx: Wegbereiter der Globalisierung. Multinationale Unternehmen der westeuropäischen Chemieindustrie in der Zeit nach dem Boom (1960er-2000er Jahre) (= Nach dem Boom), Göttingen 2023. - Staffel, Florian (Sehepunkte)

"Und das war auch so ein Knackpunkt" - Professionalisierung für die Förderung von arithmetischen Basiskompetenzen - Wienhues, Inga
Professionalisierung für eine unterstützende Lernbegleitung beim mathematischen Lernen ist ein zentrales Ziel der Lehrkräfte-Ausbildung. Im Rahmen der präsentierten Studie werden die berichteten Förderhandlungen von Studierenden während der Förderung von Kindern mit Schwierigkeiten fokussiert. Erste Erkenntnisse aus einer leitfadengestützten Interviewstudie werden vorgestellt und ein Ausblick für das weitere Vorgehen des Promotionsprojekts gegeben.